Comparative Analysis of Legal Winning Between Islamic Law & Traditional Law - Muhammad Luthfi; Lathifah Hanim (Universitas Islam Sultan Agung, 2021)
The purpose of this research is to find out about the application and things related to it, To know the views of Islamic law on marriage, and to find out the views of customary law in Kutuk Village, Undaan District, Kudus Regency about marriage. The research approach method used was sociological juridical. Writing specifications are descriptive analysis, sources and types of data used primary and secondary data. Data collection methods by interview, library research, and using qualitative data analysis methods. The conclusions of this study are: The marriage according to Islamic law is carried out very Islamic and really hopes for the pleasure of Allah SWT without being based on material. Meanwhile, the wedding according to customary law in Kutuk Village, Undaan Subdistrict, Kudus Regency is very close to the Kejawen area of Pati Regency and seems to smell of material existence. The material problem there really determines whether or not a proposal is accepted.